Cardiovascular Involvement in Sjögren’s Syndrome - Atzeni, Fabiola; Gozza, Francesco; Cafaro, Giacomo; Perricone, Carlo; Bartoloni, Elena (Frontiers in Immunology, 2022)
Sjögren Syndrome (SS) seems to be associated with a greater “overall risk” of cardiovascular (CV) and cerebrovascular events. Although not conventionally considered a feature of the disease, CV events represent a major burden in SS patients. CV risk is the consequence of a complex combination of multiple factors, including traditional risk factors and disease-related mechanisms. A complex relationships between disease-related features, endothelial dysfunction and traditional risk factor has been suggested. Several drugs are available for treating the systemic manifestations of SS, however they have shown positive effects on different outcomes of the disease, but until today the data on the role of these drugs on CV events are scarse. Given these data, the aim of this review was to evaluate the risk of CV risk in primary SS and the effect of the drugs on this manifestation.